2020
DOI: 10.1073/pnas.2019450117
|View full text |Cite
|
Sign up to set email alerts
|

Striking heterogeneity of somatic L1 retrotransposition in single normal and cancerous gastrointestinal cells

Abstract: Somatic LINE-1 (L1) retrotransposition has been detected in early embryos, adult brains, and the gastrointestinal (GI) tract, and many cancers, including epithelial GI tumors. We previously found numerous somatic L1 insertions in paired normal and GI cancerous tissues. Here, using a modified method of single-cell analysis for somatic L1 insertions, we studied adenocarcinomas of colon, pancreas, and stomach, and found a variable number of somatic L1 insertions in tumors of the same type from patient to patient.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…Whilst the DNAm of CpG islands is mostly known for tumour suppressor gene silencing, GGDHo can be conducive to altered gene expression, oncogene and retrotransposon activation [148]; functional deficiencies in structural DNA repeats [149]; genetic and chromosomal instability; and ultimately to carcinogenesis. These observations are based on substantial experimental evidence.…”
Section: Consequences Of Global Genome Dna Hypomethylationmentioning
confidence: 99%
“…Whilst the DNAm of CpG islands is mostly known for tumour suppressor gene silencing, GGDHo can be conducive to altered gene expression, oncogene and retrotransposon activation [148]; functional deficiencies in structural DNA repeats [149]; genetic and chromosomal instability; and ultimately to carcinogenesis. These observations are based on substantial experimental evidence.…”
Section: Consequences Of Global Genome Dna Hypomethylationmentioning
confidence: 99%
“…My lab has found that a minority of somatic L1 insertions in the bulk DNA of gastric and esophageal cancers are present in normal tissue (36). Likewise, we have found in single cells and whole tissue that about 15-20% of somatic insertions in colon, gastric, and pancreatic cancers are present in the noncancerous cells of these tissues (81). Are the normal cells in the normal tissue in fact normal?…”
Section: Somatic Line-1 Insertions In Cancermentioning
confidence: 54%
“…With a comprehensive approach using several of these tools, somatic cancers and neuronal tissues could be examined to determine how FL-L1Hs elements evade somatic repression in these tissues and which elements can achieve this status. Other normal epithelial and neuronal tissues in which FL-L1Hs elements can evade somatic repression also could be examined, including the esophagus, pancreas, colon ( Doucet-O'Hare et al 2015 ; Ewing et al 2015 ; Scott et al 2016 ; Yamaguchi et al 2020 ) as well as the liver, brain, embryonic stem cells, and cells undergoing neuronal differentiation ( Sanchez-Luque et al 2019 ). Aberrantly high levels of L1 expression and retrotransposition often are associated with neuronal diseases; in many cases, the underlying mechanisms leading to L1 up-regulation are unknown ( Terry and Devine 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has become clear that L1 also is active in at least some somatic tissues, including neuronal tissues of the brain ( Coufal et al 2009 ; Baillie et al 2011 ; Evrony et al 2012 ; Upton et al 2015 ; for review, see Terry and Devine 2020 ) and human cancers ( Iskow et al 2010 ; Lee et al 2012 ; Solyom et al 2012 ; Shukla et al 2013 ; Helman et al 2014 ; Tubio et al 2014 ; Doucet-O'Hare et al 2015 ; Ewing et al 2015 , 2020 ; Rodić et al 2015 ; Scott et al 2016 ; Rodriguez-Martin et al 2020 ; Yamaguchi et al 2020 ). Growing evidence also suggests that L1 can evade somatic repression in other normal cells and tissues, including the esophagus, pancreas, and colon ( Doucet-O'Hare et al 2015 ; Ewing et al 2015 ; Scott et al 2016 ; Yamaguchi et al 2020 ), as well as the liver, brain, embryonic stem cells, and cells undergoing neuronal differentiation ( Sanchez-Luque et al 2019 ). Many aspects of L1 regulation and dysregulation remain poorly understood in these diverse settings owing to a limited knowledge of the full-length L1 source elements that drive MEI mutagenesis.…”
mentioning
confidence: 99%